A new method for the analysis of signals: the Square-Wave method - Skliar, Osvaldo (2008)
The “Square-Wave Method” (SWM) presented here is a new method for the systematic analysis of signals – either locally or globally – depending on only one variable (time). The SWM is based on a technique (previously described elsewhere) for the representation of this type of signals using a sum of trains of square waves. The SWM is applied here to several analytically characterized signals and to an audio signal.